(untitled) (Journal of Applied Science and Engineering A, 2022)
Silicon-organic polymers containing thioacetamide, thiocarbamide, and dioxothiocarbamide groups were used in this investigation. The polymers were produced by the hydrolytic poly-condensation reaction of silicon-organic monomer, 3-triethoxysilylpropylamine. Au(III) sorption onto the polymers has been studied. The optimal condition of the sorption is confirmed by sorption experiments which were carried out at various times and in acidic solution conditions. Based on the result of the instrumental analysis and the values of thermodynamic parameters, such as ΔG°, ΔH°, and ΔS° can be concluded that Au(III) can be connected with the electro-donor nitrogen and sulfur atoms of the functional group of the polymer by chemical and coordination bonds.